2007
DOI: 10.1103/physrevlett.98.023401
|View full text |Cite
|
Sign up to set email alerts
|

Multiply Charged Neon Clusters: Failure of the Liquid Drop Model?

Abstract: We have analyzed the stability and fission dynamics of multiply charged neon cluster ions. The critical sizes for the observation of long-lived ions are n2=284 and n3=656 for charge states 2 and 3, respectively, a factor 3 to 4 below the predictions of a previously successful liquid-drop model. The preferred fragment ions of fission reactions are surprisingly small (2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…What is slightly surprising about the +4 results is the very small size of some of the fragment ions; however, the experiments by Mähr et al 7 on the fragmentation of multiply charged neon clusters showed a preference for dimer and trimer ions, and the imaging experiments of Hoener et al 16 showed that monomer and dimer ions were also generated during the fission of neon dication clusters. Finally, the calculations of Miller et al 38 on multiply charged clusters of Lennard-Jones particles show the ejection of individual charged particles from comparatively small clusters, but also provide evidence of a transition to more symmetric fission as the clusters increase in size.…”
Section: B Quadruply Charged Cluster Ionsmentioning
confidence: 92%
See 3 more Smart Citations
“…What is slightly surprising about the +4 results is the very small size of some of the fragment ions; however, the experiments by Mähr et al 7 on the fragmentation of multiply charged neon clusters showed a preference for dimer and trimer ions, and the imaging experiments of Hoener et al 16 showed that monomer and dimer ions were also generated during the fission of neon dication clusters. Finally, the calculations of Miller et al 38 on multiply charged clusters of Lennard-Jones particles show the ejection of individual charged particles from comparatively small clusters, but also provide evidence of a transition to more symmetric fission as the clusters increase in size.…”
Section: B Quadruply Charged Cluster Ionsmentioning
confidence: 92%
“…11 If fission results in just two fragments, then the Coulomb repulsion that accompanies their separation should lead to a significant release of kinetic energy, and estimates from previous experiments range from 0.2 to 1 eV. 1,6,7,13 However, it has been shown earlier that a simple point charge calculation of the kinetic energy release expected for a dication cluster composed of a dielectric material gives a very unrealistic estimate for the location of the two charges. 11 Apart from earlier studies of triply charged CO2 and NH3 clusters, 1,8 neither of which included any size-dependent data, there have been no recorded examples of the delayed Coulomb fission of multiply charged molecular clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental measurements of the acquired kinetic energy during the latter subprocess ranges from 0.2 to 1 eV. 5,8,11 If the complete process is not spontaneous, it is referred to as a delayed Coulomb fission. Apart from early measurements on triply charged CO 2 and NH 3 clusters, 3,12 there have been no recorded examples of delayed Coulomb fission of molecular clusters.…”
mentioning
confidence: 99%